A Crital Review of Islamic and Conventional Banking in Digital Era: A Case of Pakistan - Muzaffar Asad, Dr.; Ahmad, Israr; Hussain Haider, Syed; Rabia Salman, Dr. (International Journal of Engineering and Technology, 2018)
Islamic banking is growing at a fast pace in economies which are considered as the champions of entrepreneurship and counter interest-based monetary system. Currently, Islamic banks have touched $1 trillion and is rising around at 20% yearly. However, this rapid growth is not limited to the Muslim countries but commodities of Islamic institutions are obtaining reputation in non-Muslim countries. The purpose of this study is to understand the main differences in Islamic and conventional banking in Pakistan on the basis of cost and benefit analysis, comparison of lending structure, and comparison of risk management especially in the context of current digital era. The methodology followed in the paper is based on the review of literature and particularly the banking practices in Pakistan. In this study, it has been analyzed that how a system made by Muslim economists long ago has become a powerful reality. This study inspects the upright addendum of Islamic banking and compare it to conventional banking. Effects of the inspection are positive as the productivity and success of Islamic banks is better than that of non-Islamic banks even in current digital economies. It is useful for the practitioners and policy makers to seek guidance for strengthening of the system.Â